Strangers in Their Own Land - Arlie Russell Hochschild (Audible Studios on Brilliance Audio, 2017)
In Strangers in Their Own Land, the renowned sociologist Arlie Hochschild embarks on a thought-provoking journey from her liberal hometown of Berkeley, California, deep into Louisiana bayou country - a stronghold of the conservative right. As she gets to know people who strongly oppose many of the ideas she famously champions, Hochschild nevertheless finds common ground and quickly warms to the people she meets, among them a Tea Party activist whose town has been swallowed by a sinkhole caused by a drilling accident - people whose concerns are actually ones that all Americans share: the desire for community, the embrace of family, and hopes for their children.